Order parameter of a three-dimensional Ising-like system in the simplest and higher non-Gaussian approximations - Pylyuk, I.V. (Condensed Matter Physics, 2013)
The application of the collective variables method to the study of the behaviour of nonuniversal characteristics of the system in the critical region is illustrated by an example of the order parameter. Explicit expressions for the order parameter (the average spin moment) of a three-dimensional uniaxial magnet are obtained in approximations of quartic and sextic non-Gaussian fluctuation distributions (the ρ⁴ and ρ⁶ models, respectively), taking into account confluent corrections. Some distinctive features appearing in the process of calculating the order parameter on the basis of two successive non-Gaussian approximations are indicated. The dependence of the average spin moment of an Ising-like system on the temperature and microscopic parameters is studied. Застосування методу колективних змiнних до вивчення поведiнки неунiверсальних характеристик системи в критичнiй областi проiлюстровано на прикладi параметра порядку. Явнi вирази для параметра порядку (середнього спiнового моменту) тривимiрного одновiсного магнетика отримано в наближеннях четвiрного та шестирного негаусових розподiлiв флуктуацiй (моделi ρ⁴ та ρ⁶ вiдповiдно) з врахуванням конфлуентних поправок. Вказано на деякi вiдмiннi риси, якi проявляються пiд час розрахунку параметра порядку на основi двох послiдовних негаусових наближень. Дослiджено залежнiсть середнього спiнового моменту iзингоподiбної системи вiд температури та мiкроскопiчних параметрiв.